THE USE OF ARTICLES IN THE ENGLISH ANTHROPONYMIC SPACE - Malyk, H. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The discrepancy between the grammatical rules for the use of articles with English anthroponyms and samples of real speech activity is taken to the fore. Typical contexts of contextualizing the semantic meaning of articles in various anthroponymic models of different structures are described. Diverse antoponymic material is involved into research, which made it possible to consider the functional and semantic features of the anthropological article as a multidimensional category.